2013
DOI: 10.1016/j.expthermflusci.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of pressure-sensitive paint to low-speed flow around a U-bend of strong curvature

Abstract: Two in-house Pressure-Sensitive Paint (PSP) formulations have been developed and tested in the low-speed regime on the flow around a U-bend of strong curvature. The two PSP formulations use trisBathophenanthroline Ruthenium Perchlorate (Ru (II)) and Platinum tretakis (pentafluorophenyl) Porphyrin (PtTFPP) as their photoactive molecules, incorporated in identical sol-gel matrices. Ru (II) emits a broad peak centered at 610nm while PtTFPP emits a much narrower peak at 650nm. The paints were illuminated using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…This is evidenced by the absence of the flow features, like the spanwise vortex pair and the separation line in the surface pressure map shown in Figure 10b. Similar conclusions were also drawn by Zare-Behtash et al [38] and Quinn et al [26,34]. In fact, an interesting phenomenon can be observed by plotting the surface pressure profile, measured by the two PSPs being studied, along the centreline of the contour bump, as shown in Figure 11.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This is evidenced by the absence of the flow features, like the spanwise vortex pair and the separation line in the surface pressure map shown in Figure 10b. Similar conclusions were also drawn by Zare-Behtash et al [38] and Quinn et al [26,34]. In fact, an interesting phenomenon can be observed by plotting the surface pressure profile, measured by the two PSPs being studied, along the centreline of the contour bump, as shown in Figure 11.…”
Section: Resultssupporting
confidence: 84%
“…One of the major drawbacks in pressure measurements using pressure-sensitive paints is their temperature dependency [6,18,26]. Therefore, it is necessary to investigate the temperature sensitivity characteristics of the two polymer-based PSPs being studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34][35][36][37] The in-house developed PSP technology used in the present study has been successfully applied in a variety of flow conditions and has been found in all cases to provide accurate pressure measurements when compared to conventional pressure transducers. [38][39][40][41][42][43][44] The PSP setup consists of a LaVision Image Intense 12-bit CCD camera with a 590nm long-pass filter mounted on the lens, and UV LEDs with peak wavelength of 390nm were used for image acquisition. Ruthenium is used as the luminohpore molecules in the current recipe.…”
Section: B Measurement Techniquesmentioning
confidence: 99%